Psychological features of personality’s religious socialization: age peculiarities - Savelyuk, N. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article summarizes theoretical analysis of the concepts "socialization" and "religious socialization" which is defined as the process of "the entry of a person or group of people into a religious way of life, the assimilation of their religious values and norms of behavior, and, as a consequence, the change of relations with society caused by professed religious laws." As a result of this process, people adapt to the appropriate cultural environment and become separated from a certain part of society; reveals sociological, psychological, pedagogical approaches as the basic scientific contexts of the consideration; compares the role of main agents in religious socialization — parents, religion, different religious organizations and person’s coevals. The most widely studied ontogenetic periods of religious socialization, namely childhood, adolescence and early adolescence, are noted. At the same time, it emphasizes the period of ontogeny that has not been practically studied, such as late adolescence and periods of adulthood. And since the aforementioned age stages are a period of bright flowering of personality, which develops and manifests itself in the activity of the individual, then it is expedient to study here not so much the influence and interaction of the agents of socialization, as their own attitude, the person’s assessment of their religiosity. The role of personality’s own religious activity as the subject factor of hisreligious socialization has been substantiated. Results of the comparative empirical study on expression degree of the main aspects of religious activity in adolescence and early adulthood have been described and interpreted. It has been stated that in the majority of religious, as well as pre-religious feelings and internal motives of religiousness, with certain age, the experience has weakened due to the feeling of loneliness, the feeling of "déjà vu" and the bifurcation of personality’s religious self-consciousness between "sinful" and "righteous", and, therefore, the effectiveness of appealing to God in order to attain the desired state of well-being has intensified.